The Influence Of Entrepreneurial Spirit and Creativity On The Success Of Garutan Batik Business In District - Wahyudin, Billy Reza; Mubarok, Teten Mohamad Sapril; Lindayani, Lindayani (Entrepreneurship Faculty, Universitas Garut, 2024)
This study aims to investigate the influence of entrepreneurial spirit and creativity on the success of Garutan batik business in Garut Regency. The research method used is a quantitative approach with a non-experimental type. The participants of this study were business owners of the Garutan batik industry in Garut Regency, with a population of 34 units. The sampling technique used was Non Probability Sampling with Exhaustive Sampling type. The results showed that entrepreneurial spirit and creativity had a positive effect of 34.6% on the success of the Garutan batik industry business. The entrepreneurial spirit makes a greater contribution than creativity to business success. The results showed that the entrepreneurial spirit had a significant effect on the success of the Garutan batik business with an effect of 34.6%. Meanwhile, creativity has no effect on the success of Garutan batik business. The implication of this study is that the combination of a strong entrepreneurial spirit and skillful creativity can help in achieving a higher level of business success. The results of this study are expected to provide a deeper understanding of the factors that influence business success in batik businesses, especially in Garut Regency. The findings of this study are expected to serve as a reference for other industries in the craft subsector to improve their business success. In addition, this research can also provide benefits for the development of entrepreneurship science, both in academic and practical contexts and it is hoped that the results of this study can enrich the literature and become a foundation for further research in the field of entrepreneurship and creativity.